How Cognitive Reserve Could Protect from Dementia? An Analysis of Everyday Activities and Social Behaviors During Lifespan - Francesca Morganti; Ilia Negri (Brain Sciences)
Background/Objectives: In the last decade, there has been a notable increase in the prevalence of cognitive decline among the elderly population. This phenomenon is further compounded by the concurrent rise in life expectancy, indicating a growing concern for the health and well-being of individuals in this demographic. Dementia has become a disease with a strong social impact, not exclusively limited to its health dimension. It is generally accepted that lifestyle factors and psychological attitudes toward life challenges may serve as protective mechanisms against pathological cognitive decline. The objective of this contribution is to evaluate the impact of lifestyle factors (e.g., physical activity, employment history, nutrition, technology use, etc.), stressors (e.g., illness, rare events, abandonments, home moving, etc.), and sociability (e.g., marriage, active friend network, children proximity, work relationships, etc.) at the onset of pathological cognitive frailty. Methods: In this study, a semi-structured interview was administered to 32 individuals over the age of 65 during their initial neuropsychological evaluation for suspected dementia. Results: Linear regressions with Mini Mental State Examination scores indicated that lifestyle and sociability factors offer a degree of protection against cognitive decline, while stressors were found to be unrelated to this phenomenon. Conclusions: The utilization of contemporary technologies, the possession of a driver’s license, and the maintenance of an active social network have been demonstrated to possess a high degree of predictive value with respect to cognitive reserve in the context of aging.